Profile of Characteristic and Secondary Metabolite Content Alstonia Scholaris Medicinal Plants - Noviyanti Noviyanti; Raden Aldizal Mahendra Rizkio Samudra; Farid Perdana; Diennisa Izzati Thahira (Universitas Aisyah Pringsewu, 2021)
Pulai plant (Alstonia scholaris) has been known as a medicinal plant that is used by the community. Utilization in the field by the community usually uses boiling or brewing from the leaves and bark. The purpose of this study was to determine the characteristics and secondary metabolite content of steeping and boiling pulai plants. The method used is brewing and infusion from the leaves and bark of the pulai. The results of the research for the characteristics of this plant that met the MMI criteria were water content and total ash content, while secondary metabolites contained alkaloids, flavonoids, steroids, and triterpenoids. Abstrak: Tanaman pulai (Alstonia scholaris) memiliki dikenal sebagai tanaman obat yang dimanfaatkan oleh masyarakat. Pemanfaatan di lapangan oleh masyarakat biasanya menggunakan perebusan atau penyeduhan dari daun dan kulit batang. Tujuan dari penelitian ini adalah untuk mengetahui karaetistik dan kandungan metabolit sekunder dari seduhan dan rebusan tanaman pulai. Metode yang digunakan adalah dengan cara menyeduh dan infusa dari daun dan kulit batang pulai. Hasil penelitian untuk karakteristik tanaman ini yang memenuhi kriteria MMI yaitu kadar air dan kadar abu total sedangkan senyawa metabolit sekunder mengandung senyawa alkaloid, flavonoid, steroid, dan triterpenoid.